2019
DOI: 10.3389/fnagi.2019.00051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in-Scanner Bilateral Frontal tDCS on Functional Connectivity of the Working Memory Network in Older Adults

Abstract: Working memory is an executive memory process essential for everyday decision-making and problem solving that declines with advanced age. Transcranial direct current stimulation (tDCS) is a non-invasive form of brain stimulation that has demonstrated potential for improving working memory performance in older adults. However, the neural mechanisms underlying effects of tDCS on working memory are not well understood. This mechanistic study investigated the acute and after-effects of bilateral frontal (F3/F4) tD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 54 publications
4
59
3
Order By: Relevance
“…No improvements in behavior were observed after sham stimulation on either task difficulty level. Nissim et al (2019) identified significantly increased functional connectivity between two frontal working memory ROIs during an acute single session of active stimulation while participants performed a 2-Back task (Nissim et al, 2019). Both the prior study and the current study only demonstrated significant changes in connectivity during the more challenging 2-Back and not the less challenging 0-Back task with active stimulation.…”
Section: Discussionsupporting
confidence: 39%
See 4 more Smart Citations
“…No improvements in behavior were observed after sham stimulation on either task difficulty level. Nissim et al (2019) identified significantly increased functional connectivity between two frontal working memory ROIs during an acute single session of active stimulation while participants performed a 2-Back task (Nissim et al, 2019). Both the prior study and the current study only demonstrated significant changes in connectivity during the more challenging 2-Back and not the less challenging 0-Back task with active stimulation.…”
Section: Discussionsupporting
confidence: 39%
“…A growing body of evidence demonstrates that 2 mA produces a net increase in excitability under the anode and cathode electrodes (Batsikadze et al, 2013;Mosayebi et al, 2019;Nissim et al, 2019). We chose this montage to elicit excitability under both the anode and cathode electrodes which is supported by prior behavioral and connectivity findings with tDCS using this same montage (Nissim et al, 2019;Soyata et al, 2019). Figure 2 demonstrates a computational model of expected current flow for the bilateral frontal montage that was used in this study.…”
Section: Tdcs Parameters and Applicationmentioning
confidence: 81%
See 3 more Smart Citations